FORECASTING THE FUTURE OF ISLAMIC EDUCATIONAL MANAGEMENT STUDY PROGRAM: PROJECTION OF NEEDS FOR LECTURERS - Nurul Hudha Purnomo (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2021)
The Islamic Educational Management program in IAIN Kediri was established in 2018 so that it requires proper planning to maintain the quality of the study program education. One of the planning steps is to maintain the ratio of the students and the lecturers by projecting the needs for lecturers. The method used in this research model is quantitative methods with the projection method, namely the growth rate and the input output, the parameter numbers used are the input rate and the graduate number, the assumption in this research is target so that the total of students can increase every year. The basic data used is the total of graduates, the total of new students and the total of lecturers. This research results in the number of needs for lecturers in the future. The results of this research reveal that in 2027, the number of lecturers needed for institutional courses will be 16 lecturers, while the number of lecturers for study program courses will increase to 25 lecturers. In 2028, the number of lecturers needed for institutional courses will increase to 18 lecturers, while the number of lecturers for study program courses will be 28 lecturers. Eventually in 2029 the number of lecturers in institutional courses will increase to 20 lecturers, while the number of lecturers needed for study program courses is 30 lecturers.